Making Organic Aloe Vera Soap to Improve Bundo Kanduang Skills in Producing Environmentally Friendly Local Products DI Nagari Padang Sibusuk - Vauzia - -; Resti Fevria; Juli Supriyanti; Vivi Hendrita; Santi Diana Putri; Roni Jarlis; Fildza Arief Syuhada; Andi Alatas (Pelita Eksakta, 2025)
Soap has an important role in daily life, especially for cleaning hands from dirt, bacteria and germs caused by various activities. One plant that has great potential in making soap is Aloe vera (aloe vera). The saponin content in Aloe vera has natural antibacterial properties, making it the right choice as a raw material for making soap. Apart from being beneficial for skin health, the use of Aloe vera can also contribute to preserving the environment. In Sijunjung Regency, the use of Aloe vera-based soap is still not popular, especially among the public. Therefore, this service program aims to introduce the benefits of Aloe vera to the community and Bundo Kanduang, so that they care more about health and the environment. Developing skills in utilizing the potential of Aloe vera for making soap can be the right choice to improve the household economy. The methods used in this activity include lectures, demonstrations, questions and answers, and guided practice. Evaluation of the results of the activity showed an increase in participants' knowledge, skills and motivation in preserving the environment by using Aloe vera as a natural soap base that is environmentally friendly and has economic value